“Effects of Overcrowding in the English Language Teaching among the Students of the 1st Year of Administrative Management at "Luis Fernando Ruiz" High School” - Idrovo Pluas, Yasleidy Yelena (2023)
Student overcrowding causes numerous difficulties in the education system, such as increased discipline issues in classrooms, delayed performance of struggling students, worsening standardized test scores, higher overall noise levels, etc. Consequently, Education First English Proficiency Index [EF EPI] mentions that Ecuador has a low level of English proficiency, ranking 82nd out of 111 participating countries. That is why the present qualitative research, with a descriptive design, seeks to identify the effects of overcrowding in the English language teaching among the students of the 1st year of Administrative Management at "Luis Fernando Ruiz" High School. The techniques used were observation and interview, with the appropriate instruments being field diaries and an interview guide. The research focused on two passionate English teachers who shared their valuable insights on how overcrowding can affect English language teaching. It was determined that the classrooms are overcrowded by connecting the teachers’ perceptions, the information from the field diaries, and the bibliographic information. It was found that the average student per classroom at Luis Fernando Ruiz High School is between 40 and 45 students. It caused teachers to feel stressed, exhausted and constantly interrupted during class development due to various disciplinary issues. Furthermore, students with special needs are also affected, since insufficient time prevents their special treatment. It was considered that the maximum number of students a teacher should work with is 25. It was also noted that only a few classrooms have sufficient space. The consequences of the high number of students were deficient motivation and poor language skills development. The impacts of overcrowding are complex and multifaceted. To address the challenges posed by overcrowding and improve English language proficiency at the Luis Fernando Ruiz High School, some interventions are essential. Such as reducing class sizes optimizing the use of available technological resources, and providing additional support to teachers and students can lead to a more conducive teaching learning environment, encouraging ultimately improved language skills and academic performance